아로마테라피가 중년여성의 갱년기 증상, 스트레스 및 우울에 미치는 효과: 체계적 문헌고찰 - 김신미; 송지아; 김미은; 허명행; Kim, Shinmi; Song, Ji-Ah; Kim, Mi-Eun; Hur, Myung-Haeng (Journal of Korean Academy of Nursing, 2016)
Purpose: This study was a systematic review to evaluate the effects of aromatherapy on menopausal symptoms, perceived stress and depression in middle aged-women. Methods: Eight databases were searched from their inception September 8, 2015. Two reviewers independently performed the selection of the studies, data abstraction and validations. The risk of bias was assessed using Cochrane criteria. For analysis of the data, a meta-analysis of the studies was performed. Results: From the electronic databases, 73 articles were selected, and 19 removed due to duplication. After two reviewers read the abstracts of 54 studies, 34 studies were selected. Complete papers for 34 s were read and, 12 studies which met selection criteria were reviewed and the effects of aromatherapy on menopausal symptoms, stress and depression analyzed using meta-analysis with RevMan. In the 2 studies which included Randomized Controlled Trials testing of aromatherapy on menopausal symptoms and comparison of control and placebo groups were done. Aromatherapy massage was favorably effective in reducing the menopausal symptoms compared to the control group (n=118, MD=-6.33; 95% CI -11.51 to -1.15), and compared to the placebo group (n=117, MD=-4.14; 95% CI -7.63 to -0.64). Also aromatherapy was effective in reducing stress (n=72, SMD=-0.64; 95% CI -1.12 to -0.17) and depression (n=158, MD=-5.63; 95% CI -10.04 to -1.22). Conclusion: There is limited evidence suggesting that aromatherapy for middle-aged women may be effective in controlling menopausal symptoms, perceived stress and depression.